PERILAKU PENCARIAN INFORMASI SEBAGAI SUMBER GAGASAN PEMBUATAN BERITA OLEH WARTAWAN PIKIRAN RAKYAT - Tantyo Hamami; Dian Sinaga; Wina Erwina (Universitas Padjadjaran, 2014)
This research aims to discuss how the behavior of journalists, especially in daily news paper Pikiran Rakyat Bandung Raya rubric’s to search information as an idea in making news. The research methodology was qualitative method with case research approach. The data collection is done by in-depth interviews, observation, and literature. Informants in this research were the twelve journalists in Pikiran Rakyat Bandung Raya Rubric’s is selected by snowball sampling techniques with the help of key informants. through key informants, research’s get the next informant to be interviewed. The results of this research shows that all informants do several stages of information seeking, there are six greats stages journalist do is stage activities prefix information retrieval, stage activities of election/ selection information topics, the processing step search/ browsing information, the processing step collecting the information, the processing step presentation and a processing step which is flexible journalist that the determination of viewpoint/ news Angle. The results of this research shows that all informants through several stages information seeking. There are six stages journalist do, prefix step of information seeking, the stage of election/ selection information topics, the stage of search/browsing information, the stage of collecting the information, the stage of presentation and there is a flexible stage of journalist to determine Angle news. Penelitian ini bertujuan untuk membahas tentang bagaimana perilaku para wartawan khususnya di rubrik Bandung Raya koran harian Pikiran Rakyat dalam melakukan pencarian informasi sebagai gagasan dalam pembuatan berita. Metodologi penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan dengan wawancara mendalam, observasi, dan studi pustaka. Informan dalam penelitian ini merupakan dua belas wartawan yang ada di Rubrik Bandung Raya Pikiran Rakyat yang dipilih melalui teknik Snowball sampling dengan bantuan key informan. Melalui key informan maka peneliti mendapatkan informan selanjutnya untuk di wawancarai. Hasil penelitian ini menunjukkan bahwa semua informan melakukan beberapa tahapan pencarian informasi, terdapat enam tahapan besar yang wartawan lakukan, yaitu tahap kegiatan awal pencarian informasi, tahap kegiatan pemilihan/ seleksi topik informasi, tahap kegiatan penelusuran/penjelajahan informasi, tahap kegiatan pengkoleksian informasi, tahap kegiatan penyajian dan satu tahap kegiatan wartawan yang bersifat fleksibel yaitu penentuan sudut pandang berita.